Sounding Vessel Position From Adjustment by Variation of Parameters - Mapp, G. R.; Byrnes, H. J.; Heinzen, M. R. (The International Hydrographic Review, 2015)
For hydrographic surveys conducted by the U.S. Naval Oceanographic Office, the position of a sounding vessel is determined by applying the method of adjustment by variation of parameters. Three types of navigational aids are used: ranging, azimuthal, and hyperbolic. Given data from any combination of at least two navigational aids, a fix may be obtained using an iterative method, which applies successive adjustments to an approximate location and forces it to converge to the most probable position. The magnitude and direction of each adjustment is determined from a least squares solution that minimizes the residual differences between actual navigational observations and imaginary observations calculated as if the ship were at the approximate location.